2019
DOI: 10.1039/c9cp02308a
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of the S2-to-S3 state transition of the oxygen-evolving complex of photosystem II

Abstract: The room temperature pump-probe X-ray free electron laser (XFEL) measurements used for serial femtosecond crystallography provide remarkable information about the structures of the catalytic (S-state) intermediates of the oxygen-evolution reaction of photosystem II. However, mixed populations of these intermediates and moderate resolution limit the interpretation of the data from current experiments. The S3 XFEL structures show extra density near the OEC that may correspond to a water/hydroxide molecule. Howev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 72 publications
2
36
0
Order By: Relevance
“…The abovementioned conclusion from our TRIR data that the O1 channel serves as a single pathway of water delivery in the S 2 → S 3 transition supports the view that W3 ligated to Ca 2+ is inserted into the O6­(Ox) site and W3 is replenished by water delivery through the O1 channel. , In particular, the recent SFX study by Ibrahim et al observed significant movements of water molecules in the “water wheel” located between N298 and O1 in the S 2 → S 3 transition, suggesting that the water wheel serves as an entrance for substrate water. The effect of N298A mutation on the water transfer suggests that the structure of the water wheel plays a significant role in the water delivery mechanism.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The abovementioned conclusion from our TRIR data that the O1 channel serves as a single pathway of water delivery in the S 2 → S 3 transition supports the view that W3 ligated to Ca 2+ is inserted into the O6­(Ox) site and W3 is replenished by water delivery through the O1 channel. , In particular, the recent SFX study by Ibrahim et al observed significant movements of water molecules in the “water wheel” located between N298 and O1 in the S 2 → S 3 transition, suggesting that the water wheel serves as an entrance for substrate water. The effect of N298A mutation on the water transfer suggests that the structure of the water wheel plays a significant role in the water delivery mechanism.…”
Section: Discussionsupporting
confidence: 82%
“…Two major models have been proposed concerning the mechanism of water delivery to the O6­(Ox) site. One is that the water molecule is inserted from Ca-bound W3, which is then replenished by water delivery through the O1 channel. , The SFX studies showed that water molecules along the O1 channel were significantly altered during the S 2 → S 3 transition. , In particular, Ibrahim et al observed the changes in the positions of five water molecules designated as the “water wheel” located between O1 and D1-N298 (Figure A), suggesting its role as an entrance for substrate water. In addition, Fourier-transform infrared (FTIR) study by Debus and co-workers showed that a water molecule inserted in the S 2 → S 3 transition was affected by replacement of Ca 2+ with Sr 2+ , while our time-resolved infrared (TRIR) measurement showed that the hydrogen bonding interaction of the CO group of Y Z • was altered during this transition.…”
Section: Introductionmentioning
confidence: 99%
“…In the S 2 state, a low-spin conformer gives rise to the multiline electron paramagnetic resonance (EPR) signal centered at g = 2, whereas high-spin conformers give rise to broad featureless signals appearing at g = 4.1 to g = 4.7. ,, , In the S 3 state, multiple conformers exist that have S = 3, ,,, and a conformer having S = 6 has been proposed to correspond to a precursor form of the S 3 state having a five-coordinate Mn­(IV) ion, although in an alternate proposal, it corresponds to the glycerol-induced distortion of a six-coordinate Mn­(IV) ion . There is considerable evidence that a high-spin conformer of the S 2 state is required for the advancement to the S 3 state, ,,,, ,, but the nature of this high-spin state remains under debate (e.g., see refs , , , , and ). The prevailing view is that the low-spin conformer of the S 2 state has O5 bound to Mn4 (the “open” conformation) and that the high-spin conformer has O5 bound to Mn1 (giving rise to a cubane-like “closed” conformation). In this view, the toggling of O5 between Mn4 and Mn1 is linked to redox isomerization, with the five-coordinate Mn­(III) ion being located at the Mn1 position in the “open” conformer and at the Mn4 position in the “closed” conformer.…”
Section: Introductionmentioning
confidence: 99%
“…14,15,17,21,31 The precise mechanism for this is under debate and the three discussed options are depicted in Scheme 1. [32][33][34][35][36][37] In addition to this water uptake (denoted by a W superscript; Scheme 2), in each S state the cluster can attain at least two different conformations. 18,[38][39][40][41]56 This is best documented for the S 2 state, where the two conformations give rise to the low spin (LS) S 2 g ¼ 2 multiline and the broad high-spin (HS) g ¼ 4-6 EPR signals, respectively.…”
Section: Introductionmentioning
confidence: 99%